Pregnancy outcome in elderly primigravidae at a Nigerian Tertiary Hospital: a five-year review - Opadiran, R. O.; Isah, A. D.; Adewole, N.; Omonua, K. I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pregnancy though a physiologic process also comes with its complications. This has been found to be related to factors associated with the mother and fetus. Maternal age at first pregnancy is a determining factor which could affect pregnancy outcome. Objective of present study was to determine the effect of maternal age on obstetric outcome. Methods: A five-year retrospective case control study involving primigravid women aged 35years and above (elderly primigravidae) and the younger primigravidae aged below 35 years who delivered at the University of Abuja Teaching hospital (UATH) between 2012 and 2016. Data were collected from their case notes, antenatal and delivery registers. For comparative purposes, obstetric and perinatal parameters including antenatal, labour, delivery, postpartum factors were collected for both the elderly primigravidae and younger primigravidae. A total of 6,052 deliveries, of which 2,456 were primigravidae and 42 of them were ≥35years of age. Out of 42 cases, only 30 folders were found and analyzed. The matched controls were selected consecutively after each elderly primigravidae in the register without prior knowledge of their pregnancy outcome. The data was analyzed using SPSS version 20. Chi square test X2 and student T test were used for comparison of the two groups. Statistical significance was set at P values of ≤ 0.05 at 95% confidence interval. Results: The incidence of elderly primigravidae was found to be 1.2% in this study. There was increased risk of hypertensive disorders in pregnancy, caesarean delivery and low APGAR scores in the elderly primigravidae group but these were not statistically significant. No other differences in obstetrics and neonatal outcome were found between the two groups. Conclusions: Elderly primigravidae are at increased risk of hypertensive disorders in pregnancy and caesarean delivery than in younger primigravidae. On the other hand, neonatal outcome of the two groups were comparable.